Effective Communication and Empathy Skills in Dentistry for Better Dentist-Patient Relationships - Sushi Kadanakuppe (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Dentistry being a part of health care profession bears the responsibility of creating and nurturing good dentist-patient relationships. The doctor-patient relationships are essential component of any health care profession especially so with dentistry. Dental patients visit oral health professionals with a variety of oral health problems which hinders their quality of life. Seeking oral health services from a dentist or an oral health care professional is in most instances a necessity created by emergency dental problems which need immediate care. In other instances, especially in the recent information era where patients are highly informed, patients seek oral health services for both preventive and restorative care other than emergency dental problems.